A model metadata schema for environmental hazard models and its implementation in the PURE portal. (February 2020) - Riddick, A.T.; Heaven, R.; Royse, K.R.; Singh, A.; Hughes, A.G.
Abstract: Geohazards, e.g. floods and landslides, are increasingly resulting in loss of life and economic damage. Process models can help the understanding of the frequency and occurrence of these hazards, reducing their impact. However, models require significant resources to develop and, ideally, should be made widely available. Further, integrated modelling demands that process models are discoverable, available and, ultimately, linkable. Metadata standards are defined for data, but the equivalent for process models are not yet available as an international standard or even as accepted best practice. Requirements have been gathered for model metadata using a questionnaire and a metadata schema has been developed. The resulting schema split model code (software) and model instance (application) given that model codes are used multiple times. International data metadata standards, e.g. ISO19115, have been used for the core of the standard. The schema has been implemented via the PURE portal (www.pureportal.org ) which makes models available and forms the basis of an international standard for model metadata. Highlights: A model metadata schema is described, based on a questionnaire, data metadata and using recent published examples. It splits the metadata into code and instance as well as providing the opportunity to store metadata for linked models. The metadata schema has been used in the PURE portal: www.pureportal.org .